(untitled) - Prabhakaran, B. (New York, 1997)
Multimedia Database Management Systems presents the issues and the techniques used in building multimedia database management systems.
Phân tích thiết kế giải thuật nâng cao
Keywords: Quản lý cơ sở dữ liệu,Hệ thống đa phương tiện,Multimedia systems,Database management